2017
DOI: 10.1017/s0143814x16000283
|View full text |Cite
|
Sign up to set email alerts
|

Policy failures, blame games and changes to policy practice

Abstract: Studies examining the policy implications of elite polarisation usually concentrate on policy formulation and change, but neglect the impact of polarisation on the day-to-day application of policies. Applying the method of causal process tracing to the Swiss “Carlos” case, a blame game triggered by the reporting about an expensive therapy setting for a youth offender, this article exposes and explains a hitherto neglected, but highly important, mechanism between political elites engaging in blame generation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 39 publications
0
29
0
1
Order By: Relevance
“…Recently various studies within the political sciences have successfully adopted this in their the process tracing approach to study complex social-political systems and explain through generative mechanisms. A recent example is provided by Hinterleitner [54] who investigates a contentious case on how a political blame game around an expensive therapy setting for a youth offender in Switzerland produced elite polarisation. Another example is the research by Adams [55], who hypothesizes how the mechanism of decentralization influences various outcomes, including interjurisdictional competition and the accommodation of heterogeneous preferences.…”
Section: Contextmentioning
confidence: 99%
“…Recently various studies within the political sciences have successfully adopted this in their the process tracing approach to study complex social-political systems and explain through generative mechanisms. A recent example is provided by Hinterleitner [54] who investigates a contentious case on how a political blame game around an expensive therapy setting for a youth offender in Switzerland produced elite polarisation. Another example is the research by Adams [55], who hypothesizes how the mechanism of decentralization influences various outcomes, including interjurisdictional competition and the accommodation of heterogeneous preferences.…”
Section: Contextmentioning
confidence: 99%
“…Those studies could also systematically compare politicians' and other actors' response times to public allegations in different institutional contexts. Moreover, future studies could also investigate the potential trade-off between the effectiveness of institutional configurations in terms of blame avoidance for executive politicians and their effectiveness in terms of service delivery (Hood 2002, Hinterleitner 2017.…”
Section: Resultsmentioning
confidence: 99%
“…Although there is reason to believe that policy-makers are guided by a range of alternative motivations, blame avoidance provides a parsimonious explanation of many phenomena in executive politics. Hood (2011) offered the most systematic account of blame avoidance in executive politics and distinguishes three types of blame avoidance strategies: presentational strategies, involving the use of arguments and other methods of diverting attention from the blame takers (see also Hood 2002, Hood et al 2009, Hood, Jennings, and Copeland 2016; agency strategies, working through the apportioning of responsibility for the exercise of public tasks among various organizations (Mortensen 2013(Mortensen , 2016; and policy strategies, characterized by the selection of policy alternatives or decision routines and procedures that will minimize the attribution of agency to would-be blame takers (Hinterleitner 2017).…”
Section: The Politics Of Blame Avoidancementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the article demonstrates that these framing contests can influence the trajectories of such projects. To obtain a more detailed understanding of these framing contests and their implications for the fate of policy projects, future research should explore the use of other blame management strategies (Hinterleitner 2018;Hood 2011;Mortensen 2016;Boin et al 2010) during the implementation of these projects. A concrete example of the latter is the creation of so called 'fuzzy' governance structures (Bache et al 2015), which are often found in the organisation of complex projects and which are sometimes said to facilitate the diffusion and deflection of blame.…”
Section: Resultsmentioning
confidence: 99%